Future Research Directions Environmental, Social, and Governance (ESG) in Indonesian Commercial Banks: (A Bibliometric Analysis) - Mainata, Dedy; Pratiwi, Angrum (MALIA: Journal of Islamic Banking and Finance, 2025)
This study aims to explore the evolution of environmental, social, and governance (ESG) and banking from a research publication perspective. Design, methodology, and approach: bibliometric analysis was applied based on selected publications from the Scopus database from 2010 to 2023 with the keywords ESG and bank. This study uses a soft VOSviewer to exercise the data. The implications of this research are: first, there are several areas that have received less attention among researchers, even though they are relevant to industry, for example, the banking industry. Second, the inconsistent frequency of publications in some specialty areas may indicate that there is an unprecedented event that hinders further research; perhaps researchers can anticipate more information and advances in the industry. Third, there is a need to strengthen collaboration between industry and academia to advance research. The implication of this study is to identify and propose future research trends in the area of ESG in banks. This research is one of the pioneering studies in analyzing bibliometrics focusing on ESG in banks. Previous studies focused on financial performance and the banking industry and did not specifically address ESG. Therefore, this study highlights the research gap in ESG. The findings show that from the 141 articles analyzed, there are five disciplines that can be further developed: sustainable development, sustainability, governance approach, environmental, and banking.